International Women's Day: Celebrating women across the globe - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
This set features women from across the globe: women working directly with growing our food, planting trees on their farms, participating in building knowledge and capacity in the communities and women scientists working with agriculture and climate change research. The set is a way to highlight women on International Women's Day, 8 March, while at the same time publishing a number of blog posts on our web site. Join us in celebrating women on this day!